The threats to the individual in their family and personal life in the information society according to the 50+ age generation - Beata Stachowiak (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
Nowadays, in Poland 6 generations of people co-exist. It is the generation Y that occupies the greatest amount of analysis in the context of the information society development, the generation Y constituting presently 21% of the inhabitants of Poland. The other generations are much less frequently mentioned; for instance, generation X and baby boomers are considered to a lesser degree despite the fact that they have the bigger share in the Polish society than the generation Y. It is worth noting that it is the job market in terms of which the description of how the respective generations function is provided. What is missing though are the considerations pertaining to, for instance, the opinions on information safety or the threats related to computer crime or the changes in the manner the family functions. This paper is an attempt to present the opinions of 50+ age group in the context of the dangers emanating from the information society development and from the extensive use of ICT in one's personal and family life.